Throughput and cost‐efficient interference cancelation strategies for the downlink of spectrum‐sharing Long Term Evolution heterogeneous networks. Issue 2 (29th October 2014) - Nasri, Raouia; Latrach, Ahmed; Affes, Sofiène
Abstract: In a heterogeneous network (HetNet), small cells such as femtocells considered in this work are deployed jointly with macrocells. This new cells' layer, when added to the network, generates interference, which could hamper neighboring macro‐user equipment (MUE) and femto‐user equipment (FUE) transmissions. In fact, this interference results in degradation of the network performance. In this paper, we propose a downlink interference cancelation (DL‐IC) strategy for spectrum‐sharing Long Term Evolution (LTE) HetNet. This DL‐IC strategy aims to reduce the interference impact on users by optimizing their received signal to interference plus noise ratio (SINR) using new utility functions for both FUEs and MUEs. These utility functions allow relaxation of the cancelation ratios in order to reduce implementation complexity while maximizing SINR, QoS, and throughput. We support by different system‐level simulations that both global network performance and user experience in terms of total throughput and received SNR or link‐level throughput, respectively, are significantly enhanced. Throughput gains achievable by the new DL‐IC strategy can reach as much as 200 % against a homogeneous LTE network without IC along with an extra 48 % per additional femtocell base station against a basic spectrum‐sharing LTE HetNet without IC. These performance figures are shown to surpass those achieved by interference avoidance techniques using either power or frequency resource allocation. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Throughput gains achievable by the new downlink interference cancelation strategy for LTE networks can reach as much as 200% against a homogeneous LTE network without IC along with an extra 48% per additional femtocell base station in a basic spectrum‐sharing LTE HetNet without IC. They far exceed the timid gains offered by interference avoidance techniques.